AI-driven techniques for controlling the metal melting production: a review, processes, enabling technologies, solutions, and research challenges. (1st July 2022) - Chadha, Utkarsh; Selvaraj, Senthil Kumaran; Raj, Aditya; Mahanth, T; Praveen Vignesh, S T; Lakshmi, Pasham Janani; Samhitha, K; Reddy, Nagireddy Bharath; Adefris, Addisalem
Abstract: Artificial Intelligence has left no stone unturned, and mechanical engineering is one of its biggest consumers. Such technological advancements in metal melting can help in process simplification, hazard reduction, human involvement reduction & lesser process time. Implementing the AI models in the melting technology will ultimately help various industries, i.e., Foundry, Architecture, Jewelry Industry, etc. This review extensively sheds light on Artificial Intelligence models implemented in metal melting processes or the metal melting aspect, alongside explaining additive manufacturing as a competitor to the current melting processes and its advances in metal melting and AI implementations.